Missing the Big Picture: Platform Opacity Weaponized for Disinformation in the Twitter Files Brazil Case - Barros, Carlos Edurado; Santini, Rose Marie; Xavier, Thiago Ciodaro; Grael, Felipe; Ferreira, Fernando (AoIR Selected Papers of Internet Research, 2026)
This paper examines the implications of the Twitter Files Brazil (TFB) controversy for the debate on platform governance, focusing on issues of transparency, moderation, and sovereignty. How has the TFB case contributed to the political manipulation of platform governance and accountability? The study combines network analysis of posts from April 2024 and historical data to map accounts early flagged for coordinated inauthentic behavior (CIB) and analyze the spread of disinformation on the platform. We also analysed the top shared posts to identify disinformation claims. Our findings reveal a polarized network, split into two distinct communities: one led by far-right U.S. and Brazilian far-right and the other by Brazilian progressive influencers. It highlights the role of far-right leaders in Brazil, who leveraged accusations against the Brazilian government to delegitimize national institutions, particularly the Supreme Court. 30.34% of the accounts engaged on sharings were previously flagged for CIB. We argue that these dynamics reflect a broader pattern of platform selective transparency, which contributes to weaponize opacity and undermine democratic digital governance. The lack of transparency hides that, beyond the legal requests for platform data and moderation, X actively arbitrates removals and boosts without accountability, including falsehoods driven by political propaganda. The study highlights how digital platforms, particularly in the Global South, play a crucial role in the international spread of disinformation, linking it to critiques of digital colonialism.